The complete mitochondrial genome of Neoporphyra dentata (Bangiales, Rhodophyta) - Sung-Je Choi; Yonguk Kim; Dong-Wook Kim; Dool-Ri Oh; Yujin Kim; Donghyuck Bae (Mitochondrial DNA. Part B. Resources, 2022)
Neoporphyra dentata (Kjellman) L.-E. Yang & J. Brodie, 2020 is an economically valuable species in seaweed aquaculture in the southwest coastal regions of Korea. Here, we report the complete mitogenome information of N. dentata using Illumina Miseq platform permitted assembly of a circular mitochondrial genome of 26,807 bp from N. dentata consisting of 29.9% GC contents, 9 protein coding genes (PCGs), 2 ribosomal RNA genes (12S rRNA and 16S rRNA), 23 transfer RNA (tRNA) genes, and a non-coding region. The overall nucleotide composition was A: 38%, T: 32%, C: 14.7%, and G: 15.2%. The mitochondrial genome of N. dentata contributes to revealing the phylogenetic relationships among species of the Bangiaceae family.